Design an Electronic System for Management Educational Process by Using Cloud Computing Case Study: College of Postgraduate, Faculty of Mathematical and Computer Sciences, Jezira University: تصميم نظام إلكتروني لإدارة العملية التعليمية باستخدام الحوسبة السحابية دراسة حالة: الدراسات العليا، كلية العلوم الرياضية والحاسوب- جامعة الجزيرة - Manal Monower Ali Monower (Journal of engineering sciences and information technology, 2019)
The aim of research is to design an e-learning system for college of graduate studies at El- Jezira University and uploaded this system on private cloud to benefit from cloud computing services, and to facilitate accessing to lectures and scientific research and supervisor or faculty staff, thus make sufficient interaction between students, researchers and faculty staff on college of graduate studies at El- Jezira University. In addition to, system are reducing costs of maintaining the equipment. The researcher followed waterfall model for analysis research, also researcher after analysis was running the system in college to know the possibility of using this system, also for purpose of data collection to identify the impact of using system. After using system with the students and faculty staff, researcher was observed that 95% of those are supported the idea of applying system in college, because help them to achieved the duties by flexible and simple way. In view of the results، a number of recommendations and proposals were presented by researcher to enhance the applying of this system, and to achieve maximum benefit when adopting him in universities or in graduate studies at El- Jezira University.